Length of weaning period but not timing of vaccination affects feedlot receiving performance and health of fall-weaned, ranch-direct beef calves - M.J. Macek; J.W. Iliff; Todd W. Schmidt; L.A. Pacheco; K. C. Olson; John R. Jaeger; Daniel U. Thomson (Kansas Agricultural Experiment Station Research Reports, 2010)
Weaning and preconditioning programs are thought to be crucial to calf health and performance during the finishing period. The stress of maternal separation, changes in diet, environmental changes, and exposure to unfamiliar pathogens increase susceptibility of recently weaned calves to bovine respiratory disease. Vaccination programs are implemented near weaning to decrease the incidence of respiratory disease. Many vaccination strategies are practiced by cow-calf producers in the United States. The most cautious strategy involves vaccination against respiratory disease pathogens 2 to 4 weeks before maternal separation followed by a booster at weaning. This strategy is used in instances in which time, labor, and facilities are available to gather and process calves while they are still suckling. Another common strategy is to defer vaccination until after calves have been shipped to a feedlot. Deferring vaccination until arrival in feedlots is thought to increase incidence of respiratory disease compared with vaccination programs implemented at the ranch of origin. This assumption has not been widely scrutinized for native Kansas cattle that are finished in Kansas feedlots.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Weaning; Feedlot; Performance